Essays in industrial organisation - Rhodes, A (2010)
This thesis presents four largely independent essays on industrial organisation. The first three essays examine how search and switching costs distort competitive markets, whilst the fourth essay studies how firms themselves might eliminate competition by agreeing to fix the market price. The key insight from the first two essays is that by choosing to pay a search cost, a consumer reveals to a retailer some private information about their product valuations. In this context the first essay re-examines the well-known theoretical Diamond Paradox in which markets completely break down if firms sell only a single product. I demonstrate that multiproduct retailers offer an elegant and realistic way of overcoming this Paradox, and then apply the model to supermarkets. In particular, this essay provides new insights into why convenience stores charge high prices and why grocery stores use selected loss-leaders. The second essay looks at internet search and therefore focuses on the special case in which search frictions become very small. It seeks to explain why retailers pay so much for online advertising, when consumers can easily click on whichever links they like. I show that if consumers have prior information about products, their search behaviour is limited but very informative about their preferences. This places prominent firms in a privileged position, and makes them substantially more profitable. The third essay provides a simple model in which small switching costs are pro-competitive and beneficial to consumers. This challenges the conventional wisdom, but also argues that switching costs should be less of a policy priority than search costs. The final essay examines a game in which two firms bargain over a collusive price. It is shown that entry into such a market may make collusion easier, and may increase price.